2020
DOI: 10.1021/acschembio.9b00794
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic Phosphodiester-Substituted Neoglycoconjugates as Ligands for Antibodies and Acute Phase Proteins

Abstract: Zwitterionic modifications of glycans, such as phosphorylcholine and phosphoethanolamine, are known from a range of prokaryotic and eukaryotic species and are recognized by mammalian antibodies and pentraxins; however, defined saccharide ligands modified with these zwitterionic moieties for highthroughput studies are lacking. In this study, we prepared and tested example mono-and disaccharides 6-substituted with either phosphorylcholine or phosphoethanolamine as bovine serum albumin neoglycoconjugates or print… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Amongst the lower molecular weight N-glycans, the anti-mannose 100-4G11-A antibody ( 32 ) bound, as expected, fractions containing Man 3–5 GlcNAc 2 and Man 3 GlcNAc 2 Fuc 1–2 . The TEPC-15 IgA antibody and the pentraxin C-reactive protein bound almost all of the fractions judged to contain phosphorylcholine-modified N-glycans in keeping with their known specificity ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the lower molecular weight N-glycans, the anti-mannose 100-4G11-A antibody ( 32 ) bound, as expected, fractions containing Man 3–5 GlcNAc 2 and Man 3 GlcNAc 2 Fuc 1–2 . The TEPC-15 IgA antibody and the pentraxin C-reactive protein bound almost all of the fractions judged to contain phosphorylcholine-modified N-glycans in keeping with their known specificity ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the lower molecular weight N-glycans, the anti-mannose 100-4G11-A antibody ( 50 ) bound, as expected, fractions containing Man 3-5 GlcNAc 2 and Man 3 GlcNAc 2 Fuc 1-2 . The TEPC-15 IgA antibody and the pentraxin C-reactive protein bound almost all of the fractions judged to contain phosphorylcholine-modified N-glycans in keeping with their known specificity ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In order to screen for antibodies against these unique glycosylation motifs, mono- and disaccharides were synthesized with these modifications, coupled to BSA, and printed in microarrays. Profiling experiments revealed that these glycan antigens were recognized by IgG and IgM in sera of dogs and pigs, 193 including those infected with Dirofilaria immitis , Ascaris suum , and Oesophagostomum dentatum . 193 Dogs infected with A. suum have also been found to possess IgM and IgG antibodies to a wide variety of other nematode glycans, including those with motifs involving LDN, LDNF, glucuronylation, polyfucosylation and unusual chitobiose-containing glycans.…”
Section: Infectious Diseasementioning
confidence: 99%
“…Profiling experiments revealed that these glycan antigens were recognized by IgG and IgM in sera of dogs and pigs, 193 including those infected with Dirofilaria immitis , Ascaris suum , and Oesophagostomum dentatum . 193 Dogs infected with A. suum have also been found to possess IgM and IgG antibodies to a wide variety of other nematode glycans, including those with motifs involving LDN, LDNF, glucuronylation, polyfucosylation and unusual chitobiose-containing glycans. 194 Some of these antigenic epitopes are shared by Schistosoma species.…”
Section: Infectious Diseasementioning
confidence: 99%